Association of Gut Microbiota and Biochemical Features in a Chinese Population With Renal Uric Acid Stone - Cao, Cheng; Fan, Bo; Zhu, Jin; Zhu, Na; Cao, Jing-Yuan; Yang, Dong-Rong (Frontiers in Pharmacology, 2022)
Previous studies suggest that patients with nephrolithiasis exhibit dysbiosis in their gut microbiota, but those studies were conducted in calcium oxalate stone patients. We aimed to explore the association of gut microbiota and biochemical features of renal uric acid stone(UAS) patients in a Chinese population and identify the related bacteria that may affect the pathopoiesis of UAS. A case-control study of 117 patients with UAS, 123 patients with gout and 135 healthy controls were included from January 2014 to October 2020. For each subject, data on demographics, biochemical parameters of blood and urine were analyzed. 15 patients with gout, 16 patients with UAS, 17 UAS patients with gout, and 17 healthy subjects were enrolled and provided fecal samples. The characteristics of gut microbiota were explored by using 16S ribosomal RNA (rRNA) gene sequencing and analyzed by using a combination of software mother and R. Hyperuricemia was the main risk factor for development of gout as well as UAS. Obesity, dyslipidemia and aciduria were unique risk factors for UAS patients. The richness,diversity and relative abundance of dominant bacteria at the phylum and genus levels of gut microbiota in UAS patients were significantly distinct from other subjects. Abundance of Bacteroides and Fusobacterium were significantly positively correlated with the serum uric acid (UA) level of UAS patients. Fusobacteria was involved in the metabolism and degradation of certain short-chain fatty acids, amino acids and sugars in pathopoiesis of UAS, and inhibited their synthesis pathways. Fusobacteria may be related to the pathogenesis of UAS, and this finding contribute to the personalized treatment of UAS from the perspective of maintaining micro-ecological equilibrium in gut.